ANALISIS PROFITABILITAS TERHADAP HARGA SAHAM SYARIAH : Perusahaan Listed Indeks Saham Syariah Indonesia (ISSI) - Fitri Utami; Edi Jatmiko; Moh. Abdur Rohman Wahid (LPPM STAI DARUSSALAM LAMPUNG, 2021)
Abstract The purpose of this research is determined the relationship of ratio profitability to the Islamic stock price of company’s listed on the Indonesian Sharia Stock Index (ISSI) 2016-2018. This research method is a quantitative study using financial report summary data provided by the IDX. The analysis technique used is multiple linear regression analysis through the classical assumption test and hypothesis test: t-test, F-test and the coefficient of determination (R2). The population in this study is all company’s listed on the Indonesian Sharia Stock Index (ISSI). The samples of this study are : the companies is consistently registered at ISSI in 2016-2018, companies that have complete financial report summary data provided by the IDX in 2016-2018, and companies that never conducted a stock split in 2016-2018. The result of regression analysis showed that simultaneously the profitability ratios of ROA, ROE, NPM, and EPS have significant effect on Islamic stock prices. While for partially only the profitability ratios of ROE, NPM, and EPS have a significant effect on stock prices. However the ROA ratio showed hasn’t significant effect on Islamic stock price. The research also shows that the stock price can be explained by a profitability ratio of 61% and the remaining 39% is influenced by other variables not included in the study.